O efeito da aplicação do SNC no capital próprio – evidência em 50 empresas sujeitas a revisão legal de contas - Pires, Amélia M.M. (2013)
With the approval of the Sistema Normalização Contabilística (SNC), will come into force after 1st January of 2010, the purpose of this study is to analyze and evaluate the impact of SNC application on equity value. Select for this purpose 50 companies audited. The results indicate a considerable part is which (66%) had not impacts. That some items of the balance show some impacts. We emphasize the item of government subsidies and intangible assets. Additionally, the study does not suggest a significant impact in the quality of financial reports, especially in disclosures.